Role of integrons in the proliferation of multiple drug resistance in selected bacteria occurring in poultry production. Issue 2 (3rd March 2020) - Racewicz, P.; Majewski, M.; Madeja, Z. E.; Łukomska, A.; Kubiak, M.
ABSTRACT: 1. The increase in microbial resistance, and in particular multiple drug resistance (MDR), is an increasing threat to public health. The uncontrolled use of antibiotics and antibacterial chemotherapeutics in the poultry industry, especially in concentrations too low to cause inhibition, and the occurrence of residues in feed and in the environment play a significant role in the development of resistance among zoonotic food-borne microorganisms. 2. Determining the presence and transmission methods of resistance in bacteria is crucial for tracking and preventing antibiotic resistance. Horizontal transfer of genetic elements responsible for drug resistance is considered to be the main mechanism for the spread of antibiotic resistance. 3. Of the many well-known genetic elements responsible for horizontal gene transfer, integrons are among the most important factors contributing to multiple drug resistance. The mechanism of bacterial drug resistance acquisition through integrons is one of the essential elements of MDR prevention in animal production.